posted by .

convert the polar equation to rectangular form.

1.) r sec(theta) = 3
2.) r = 4 cos(theta) - 4 sin(theta)

convert from rectangular equation to polar form.
1.) x^2 + (y-1)^2 = 1
2.) (x-1)^2 + (y+4)^2 = 17

1)r=3cos(theta)
r^2=3rcos(theta)
x^2+y^2=3x
2)r=4cos(theta)-4sin(theta)
r^2=4rcos(theta)-4rsin(theta)
x^2+y^2=4x-4y
x^2-4x +y^2+4y =0
x^2-4x+4+y^2+4y+4=4+4
(x-2)^2 +(y+2)^2=8

1)x^2+(y-1)^2=1
x^2+y^2-2y+1=1
x^2+y^2=2y
r^2=2rsin(theta)
r=2sin(theta)
2)(x-1)^2+(y+4)^2=17
x^2-2x+1+y^2+8y+16=17
x^2+y^2=2x-8y
r^2=2rcos(theta)-8rsin(theta)
r=2cos(theta)-8sin(theta)

thank you soooooooooo much

## Similar Questions

1. ### math

change equations to polar form: 1) y= -1 2) x^2 + y^2 = 4 how would i do these questions?
2. ### precalculus

5x+3y=8 convert each rectangular equation to polar form Convert each polar equation to rectangular form: a r=9cos0 b r=5 c rsq= cos 20 d r= 3____ 3+sin 0 Is this a test?
3. ### Polar to Rectangular Form

The letters r and theta represent polar coordinates. Write each equation in rectangular coordinates (x, y) form. Let t = theta (1) r = sin(t) + 1 (2) r = sin(t) - cos(t)
4. ### Calculus

I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
5. ### precalculus

convert the equation y^2 = 2x -x^2 into polar form. convert the equation r = 2tan(theta) into rectangular form. I'm not really sure what either of these mean. I vaguely understand polar coordinates, but I'm not sure how to convert …
6. ### Pre-Calculus

translate this polar equation into a rectangular form: rsin(2theta)=sin(theta) My answer: r2sin(theta)cos(theta)=sin(theta) 2rcos(theta)=1 2x=1 x=1/2 This is the only answer I can get and someone told me it's wrong. Would someone please …
7. ### PRECALCULUS

convert the polar equation to rectangular form. 1.) r sec(theta) = 3 2.) r = 4 cos(theta) - 4 sin(theta) convert from rectangular equation to polar form. 1.) x^2 + (y-1)^2 = 1 2.) (x-1)^2 + (y+4)^2 = 17